2021
DOI: 10.3389/feduc.2021.738790
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Theory of Planned Behavior to Identify Variables Related to Academic Help Seeking in Higher Education

Abstract: Universities admit and enrol increasingly diverse student cohorts with varying academic entry standards. To increase student success, universities offer academic support to students, however, often students do not engage in or access this academic support. Building on the Theory of Planned Behavior and a comprehensive literature review, this study aims to identify personality variables, background variables and variables related to the Theory of Planned Behavior that can predict academic help seeking in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Even while this study suggests that the TPB may be integrated in educational settings ( Patterson, 2001 ; Stanec, 2009 ; MacFarlane and Woolfson, 2013 ; Heuer and Kolvereid, 2014 ; Cooper et al, 2016 ; Burns et al, 2018 ; Dunn et al, 2018 ; Bornschlegl et al, 2021 ) and used to explain integrative-qualitative conduct in preschool settings, it also emphasizes the need for more qualitative research on the beliefs that surround this behavior in early childhood education and care.…”
Section: Theoretical Framework—theory Of Planned Behaviormentioning
confidence: 93%
“…Even while this study suggests that the TPB may be integrated in educational settings ( Patterson, 2001 ; Stanec, 2009 ; MacFarlane and Woolfson, 2013 ; Heuer and Kolvereid, 2014 ; Cooper et al, 2016 ; Burns et al, 2018 ; Dunn et al, 2018 ; Bornschlegl et al, 2021 ) and used to explain integrative-qualitative conduct in preschool settings, it also emphasizes the need for more qualitative research on the beliefs that surround this behavior in early childhood education and care.…”
Section: Theoretical Framework—theory Of Planned Behaviormentioning
confidence: 93%
“…Using drawings to Understand Students’ Help-Seeking Behavior To explore undergraduate students’ help-seeking behavior about writing papers that require research 220 undergraduate students Quantitative Results indicated that students usually receive help from peers and family members after drafting papers. Research-related tasks are the most challenging, but librarians are rarely sought for help 37 7 Bizuneh [ 91 ] (2022) Ethiopia Belief in counseling service effectiveness and academic self-concept as correlates of academic help-seeking behavior among college students To examine the association between homework practices of college students, motivation, self-regulation of learning, and final course grades 133 college students drawn from a small private college in urban New York Quantitative Results indicated that using homework logs and considering self-efficacy, motivation, and help-seeking strategies related to homework completion can promote self-directed learning 30 8 Bornschlegl [ 92 ] (2021) Australia Application of the theory of Planned Behavior to identify variables related to academic help seeking in higher education To identify personality variables, background variables, and variables related to the Theory of Planned Behavior that can predict academic help-seeking in higher education to inform the design of engaging and accessible academic support 430 students participated in the survey Quantitative The study found that only a small portion of the variance of academic help-seeking behavior could be explained, indicating the need for interventions to increase help-seeking 39 9 Bornschlegl [ 93 ] (2022) Australia Increasing accessibility to academic support in higher education for diverse student cohorts To clarify why students (do not) engage in support and what could be changed to make services more accessible and engaging ...…”
Section: Table A1mentioning
confidence: 99%